FROM TEXT TO PERFORMANCE: A BIBLIOMETRIC EXPLORATION OF LITERATURE'S ROLE IN PERFORMING ARTS - Cherian, Bindu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the significant role of literature in performing arts through a comprehensive bibliometric analysis using Scopus as the primary database. Literature provides the foundation for performing arts, offering narratives, themes, and characters that inspire theatrical, musical, and dance expressions. The analysis, conducted using Biblioshiny and VOSviewer, examines key aspects such as annual scientific production, most relevant authors, and prominent sources. Results reveal an increasing trend in scholarly output, with an annual growth rate of 7.33% from 1968 to 2023. The United States leads in research contributions, followed by the United Kingdom and Australia, while emerging players like Indonesia highlight growing global interest. A co-occurrence analysis of keywords identifies six thematic clusters, emphasizing interdisciplinary connections with health, education, and cultural heritage. Trend topics have shifted from foundational discussions on drama and music to modern themes such as mental health, creativity, and higher education. The thematic map underscores motor themes like dance and creativity, as well as niche areas like corporate theatre and music therapy. Collaboration analysis reveals strong international partnerships, with Western nations serving as major hubs and growing contributions from Asian countries. This study highlights the enduring impact of literature in advancing performing arts and its evolving relevance across diverse research domains.